Czesław Miłosz i Walt Whitman: przekład jako prawdziwa obecność - Van Nieukerken, Arent (Poznańskie Studia Polonistyczne. Seria Literacka, 2012)
Miłosz’s later poetry attempts to overcome the (post)modernist gap between the author as a textual effect and the subject of autobiography. An important stage on this road was his poetry book (in fact, a long poem in its own right) Nieobjęta ziemia [Unattainable Earth]. Its form is clearly dialogical. The collection mixes authorial poems with various examples of “heteroglossia”. Particularly striking is the prominent presence of Walt Whitman’s poetry. Whitmanian poetics assume that fully experiencing reality presupposes the existence of a community. The task of poetry consists in conceiving artistic structures that, when they are “concretized”, allow the reader to participate in such a community. Nieobjęta ziemia tries to come to terms with the Whitmanian challenge. The poetical subject in this somewhat modified example of the modern “sylva rerum” experiences its link with the “other” by an individual reception of artifacts that point to the communal essence of humanity. Nieobjęta ziemia , realizing community in the field of poetics “performatively”, incorporates these artifacts into the text. Particularly important seems to be the role played by poems translated by Miłosz himself (they are explicitly labeled as translations), and that represent the human condition called by Whitman “en masse”.